2017
DOI: 10.1111/cpsp.12191
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and Health Impact: The Examples of Cardiovascular Disease and Type 2 Diabetes Mellitus in Adults

Abstract: Child maltreatment is associated with increased risk for an array of mental and physical health problems. We reviewed studies examining associations of child maltreatment, assessed either alone or in combination with other adversities, with cardiovascular disease (CVD) and Type 2 Diabetes. PubMed was searched for relevant studies until December, 2015. Forty publications met inclusion criteria. Consistent positive associations were noted across a range of childhood adversities. Child maltreatment was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
133
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(142 citation statements)
references
References 96 publications
(155 reference statements)
8
133
0
1
Order By: Relevance
“…5,16,17 A recent systematic review found that childhood maltreatment was associated with CVD (myocardial infarction, stroke, ischemic heart disease, coronary heart disease) in 91.7% (22 of 24) of published studies. 16 Research has also examined the relation between childhood adversity and risk factors for cardiometabolic disease. For example, several studies suggest that childhood adversity is associated with increased risk of hypertension and high blood pressure levels, although findings are mixed.…”
Section: Influence Of Childhood Adversity On Cardiometabolic Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…5,16,17 A recent systematic review found that childhood maltreatment was associated with CVD (myocardial infarction, stroke, ischemic heart disease, coronary heart disease) in 91.7% (22 of 24) of published studies. 16 Research has also examined the relation between childhood adversity and risk factors for cardiometabolic disease. For example, several studies suggest that childhood adversity is associated with increased risk of hypertension and high blood pressure levels, although findings are mixed.…”
Section: Influence Of Childhood Adversity On Cardiometabolic Outcomesmentioning
confidence: 99%
“…For example, several studies suggest that childhood adversity is associated with increased risk of hypertension and high blood pressure levels, although findings are mixed. 5,16,18 Other studies also suggest that there may be an association between childhood adversity and obesity. 3,19,20 A recent meta-analysis noted a positive association between childhood adversity and childhood-overweight measures in a pooled estimate of reviewed longitudinal studies.…”
Section: Influence Of Childhood Adversity On Cardiometabolic Outcomesmentioning
confidence: 99%
See 3 more Smart Citations